INSTRUMENTING EDUCATION AND RETURNS TO SCHOOLING IN INDONESIA - Purnastuti, Losina (Jurnal Economia, 2013)
Abstract: Instrumenting Education and Returns to Schooling in Indonesia. This paper provides estimates of the profitability of investment in education in Indonesia, using IV approach and data for IFLS-4 (2007-2008). It also explores an alternative framework for assessing the present value of the financial gains from an extra year of schooling. This study finds that considering endogeneity bias via the IV method is important, and draws attention to family background factors being useful instruments. Another finding from this study that needs to be highlighted is that the benefit of continuing at school for an extra year is quite high.   Keywords: Instrumental Variable, Returns to Schooling, Education Investment   Abstrak: Instrumentasi Pendidikan dan Tingkat Pengembalian Investasi Pendidikan di Indonesia. Artikel ini menyajikan estimasi keuntungan investasi pendidikan di Indonesia dengan menggunakan data IFLS-4 (2007-2008). Kajian ini mengeksplorasi pendekatan alternative untuk menghitung present value keuntungan finansial dari tiap tambahan satu tahun pendidikan. Hasil penelitian ini menunjukkan pentingnya mempertimbangkan bias endogeniti melalui metode IV. Ditemukan pula faktor latar belakang keluarga merupakan instrument yang bermakna. Temuan lain yang tidak kalah pentingnya adalah bahwa keuntungan finansial dari tiap tambahan satu tahun pendidikan cukup besar.   Kata kunci: Variabel Instrumen, Pengembalian Investasi Pendidikan, Investasi Pendidikan.